Greenlanders Seen Through the Eyes of Signe Rink - Langgård, Karen (Nordlit, 2007)
Signe Rink (1836-1909) published four volumes of fiction in Danish, all of them stories from Greenland of the 19th century: Grønlændere. 1886 (155 pages); Grønlændere og Danske i Grønland. 1887 (204 pages); Koloni-idyler. 1888 (262 pages) and Fra det Grønland som gik. Et par Tidsbilleder fra Trediverne. 1902 (264 pages). Some of the stories are short, some are not short at all, actually, e.g. Rink 1902 consists only of two parts, the first one 205 pages long. The focus here will be on this fiction written by Signe Rink: a case study in how genres of fiction might open up for the possibility of going beyond the dominant discourse and for instance throw light at the role played by Greenlanders in colonial Greenland of the 19th century, and how it might be possible now a century later to disentangle the threads of different discourses, through reflectiveresearch - drawing on historical studies, anthropology, cultural studies and post-colonial studies.
Keywords: Signe Rink; Grønland; Grønlændere (1886); Grønlændere og Danske i Grønland (1887); Koloni-idyler (1888); Fra det Grønland som gik. Et par Tidsbilleder fra Trediverne (1902)